A battery hardware–in–the–loop setup for concurrent design and evaluation of real–time optimal HEV power management controllers. (15th November 2013) - Razavian, Reza Sharif; Azad, Nasser L.; McPhee, John
We have developed a battery hardware–in–the–loop (HIL) setup, which can expedite the design and evaluation of power management controllers for hybrid electric vehicles (HEVs) in a novel cost– and time–effective manner. The battery dynamics have a significant effect on the HEV power management controller design; therefore, physical batteries are included in the simulation loop for greater simulation fidelity. We use Buckingham's Pi Theorem in the scaled–down battery HIL setup to reduce development and testing efforts, while maintaining the flexibility and fidelity of the control loop. In this paper, usefulness of the setup in parameter identification of a simple control–oriented battery model is shown. The model is then used in the power management controller design, and the real–time performance of the designed controller is tested with the same setup in a realistic control environment. Test results show that the designed controller can accurately capture the dynamics of the real system, from which the assumptions made in its design process can be confidently justified.